Development of Computational Research Methods and Application in Chemistry - Khadka, Deba Bahadur (NUTA Journal, 2018)
The development of computational research methods and its application in chemistry has been described in this paper. Based on theoretical review on computational research, the study applied experimental research method. The discussion of findings showed that, the development of computational research methods have both advantages and disadvantages that have clearly highlighted in this study.